エンドセリンETB受容体拮抗薬による アストロサイト由来因子の発現調節を介した頭部外傷後の脳浮腫に対する抑制効果 - 田邉, 彩美; 龍, 亮太朗; 辻内, 優; 小山, 豊; 井上, 杏奈; 道永, 昌太郎; 三宅, 大助; 岩根, 綾; 山本, 隼人; 中谷, 隆聖; 湊, 由紀子; 福留, 千裕; et al. (日本薬理学会年会要旨集, 2019)
Brain edema is a critical condition resulted from blood-brain barrier (BBB) disruption after traumatic brain injury (TBI). Several astrocyte-derived factors are involved in BBB function. We previously confirmed the involvements of endothelin ETB receptor for BBB disruption. In this study, the effects of BQ788, an ETB receptor antagonist on brain edema and astrocyte-derived factors were examined. As a model of TBI, fluid percussion injury (FPI) was performed on mouse cerebrum. BBB disruption and brain edema were evaluated by Evans blue extravasation and brain water content, respectively. Expressions of astrocyte-derived factors were confirmed by Real-time PCR and immunohistochemistry. To confirm therapeutic efficiencies, intraventricular (i.c.v., 15 nmol/day) or intravenous (i.v., 5 mg/kg/day) administration of BQ788 were performed from 2 to 5 days after FPI. BQ788 ameliorated FPI-induced BBB disruption and brain edema but not affected blood pressure. ETB receptors were mainly distributed in astrocytes and BQ788 appropriately controlled expressions of several astrocyte-derived factors after FPI. Thus, blockade of ETB receptor is expected to be a novel therapeutic strategy for brain edema.